A variational formulation for relativistic mechanics based on Riemannian geometry and its application to the quantum mechanics context - Botelho, Fabio Silva (Ciência e Natura, 2018)
This article develops a variational formulation for  relativistic quantum mechanics. The main results are obtained through a connection between relativistic and quantum mechanics. Such a connection is established through basic concepts on Riemannian geometry and related extensions for the relativistic context.